Computer Based Technology And Classroom Assesment - Ayu Mustika Sari; Ambiyar; Ishak Aziz (International Journal Of Humanities Education and Social Sciences (IJHESS), 2021)
This study aims to identify and understand the computer based technology and classroom assessment. Computers can also help provide students with greater access to test items, maintain records, and explore data . The method used in this study uses a library method or approach (library research). Data obtained through observation and literature study. The results showed that The five ways in which computers can assist teachers with formative assessment during instruction. These uses include diagnosing students’ misconceptions, polling the class about their knowledge, recording students’ writing process, providing formative feedback on student products, and observing students as they work on assignments diagnosing.